God: myths of the male divine - Leeming, David Adams (Oxford University Press, 1996)
Illustrating their points with materials ranging from the prehistoric cave paintings to the mystic Jewish Kabbalah, from the ancient Indian Vedas to tales of the North American Indians and other myths from around the world, Leeming and Page reveal the changing mask of the male divine. We see how that divinity emerged in some areas from cults involving "animal masters" (as in the Bear Man of the Cherokee Indians), sorcerers, and shamans who embarked on spirit journeys. God sometimes appeared as the trickster - as Loki of the Norse people, Legba of Africa's Yoruba, Raven and Coyote of North America, and Krishna of India - both creative and bedeviling